Perbedaan status gizi bayi usia 6-9 bulan yang diberi MPASI buatan pabrik dan rumah - Erizvina Marisa Anggraeni; Dewi Marhaeni Diah Herawati; Viramitha Kusnandi Rusmil; Tisnasari Hafsah (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
The differences of nutritional status of 6-9 months old infant given factory-made and homemade complementary foodsBackground: The nutritional status of 6-9 months old babies depend on the amount of nutrition acquired from breastmilk and complementary food. The incorrect feeding of complementary food may contribute to poor nutritional status. Objective: This study aims to illustrate the nutritional status of factory-made and homemade complementary food, and analyze the difference in the nutritional status of infants given factory-made and homemade complementary food.Methods: This is an analytic, observational, and cross-sectional study, conducted in seven villages within the scope of Puskesmas Jatinangor, Jatinangor Sub-district, Sumedang Regency in August-October 2018. The samples were 102 babies 6-9 months old obtained through total sampling. The variables of this study include the type of complementary food, and infant nutritional status with weight for age, length for age, and weight for height index.Results: Complementary food consumption is dominated by factory-made type (69.6%). Macronutrients which are energy and protein and micronutrients which are vitamins from both types of complementary food already fulfill the daily recommended dietary allowances for babies, except for minerals which are calcium, iron, and zinc. Chi-Square test results showed an insignificant difference in the nutritional status of babies (p=0,881 for BW/A; p=0.194 for BH/A; and p=0,599 for BW/BH) based on the type of complementary food given.Conclusions: Nutritional contents of macro and micronutrients from both types of complementary food have fulfilled the recommended dietary allowances for complementary food, except for the minerals calcium, iron, and zinc. There wasn’t a considerable difference in nutritional status between those acquired through factory-made and homemade complementary food.